Discrimination in a multiethnic environment - the importance of intergroup contact, social distance and ethnic identity - Mihić, Vladimir; Dronjak, Olivera (Psihološka istraživanja, 2023)
Education of ethnic minorities in Serbia (and not only here) is often linked to the question whether ethnic minorities should  be educated only in their native language, and, even more importantly for the field of intergroup relations, whether this education should be, and how, integrated into mainstream education. Serbian education systems offers ethnic minorities only two options: education fully in Serbian or education fully in their own language. In some regions, even the schools themselves are separated, so the children have even less contact wit the out-group. This paper deals with the issue of the importance of intergroup contact, social distance and ethnic identity for the discrimination of the outgroup. The sample consisted of 795 children age 14 do 19 from Vojvodina. Out of those, 371 were Serbs, 240 Hungarians and 184 Slovaks. The instruments used were Ethnic identity scale (measuring ethnic pride and belief in ethnic superiority), Social distance scale and scale measuring tendency for discrimination in children`s everyday lives. We also measured frequency of contact with the outgroup. The results show that the regression model was significant (F(5,758)=77,29; p< .001; R²=0,33) and that all of the predictors were significant: Social distance (β=.33; p< .001), frequency of contact with outgroup (β=-.24; p< .001), belief in ethnic superiority (β=.19; p< .001) and ethnic pride (β=-.11; p< .05).